Aspek Hukum Penggunaan Ultrasonografi (USG) oleh Bidan dalam Praktik Kebidanan di Indonesia: Sebuah Kajian Literatur - Destri Maya Rani (LPPM POLBITRADA, 2024)
The use of Ultrasound (USG) by midwives in midwifery practice in Indonesia has become an important issue in relation to legal aspects, especially due to the absence of clear regulations governing the authority of midwives in using this technology. This study aims to review the literature on regulations, authority, and potential legal risks associated with the use of USG by midwives. The research method employed is a normative legal approach with an analysis of relevant secondary literature. The results of the study indicate that although midwives play a crucial role in maternal and child health management, the use of USG by midwives is not yet clearly regulated in the current legislation. This creates a regulatory gap that could potentially lead to legal risks for midwives. The study suggests the need for strengthening regulations, training, and clear national certification to ensure that midwives can use USG safely and in accordance with applicable legal standards in Indonesia. Keywords: ultrasound, midwife, legal aspects, regulations